Electrolyte for ultra-thin electrolytic copper foil, ultra-thin electrolytic copper foil and preparation method thereof
By adding copper sulfate, inorganic acid, additive, complexing agent, conductive polymer and hydrolyzed collagen to the electrolyte of the extremely thin electrolytic copper foil, and performing electrochemical deposition and passivation treatment, the extremely thin electrolytic copper foil is solved. The problems of high tensile strength, low roughness and oxidation resistance have achieved a double breakthrough in copper foil.
Patent Information
- Application Number
- CN202211724701.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-30
AI Technical Summary
In the field of extremely thin electrolytic copper foils, especially in copper foils with thicknesses less than 6 microns, it is difficult to achieve high tensile strength, low roughness, excellent oxidation resistance and high elongation at the same time, and it is easy to apply the negative electrode active material when coating it Break and fall off.
Using an electrolyte containing copper sulfate, inorganic acid, additive, complexing agent, conductive polymer and hydrolyzed collagen, copper foil is deposited on the cathode roller through electrochemical reactions, controlling the electrolyte component concentration and electrodeposition process parameters, combined with Passivation treatment is used to improve the mechanical properties and oxidation resistance of copper foil.
It significantly reduces the thickness and roughness of the copper foil, improves the tensile strength and elongation, realizes the extremely thin, high mechanical properties and good oxidation resistance of the copper foil, solves the problem of tearing the cathode roller, and does not tear it Continuous production is achieved under the circumstances of edges.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytic copper foil, and in particular to an electrolyte of an ultra-thin electrolytic copper foil, an ultra-thin electrolytic copper foil and a preparation method thereof. Background Art
[0002] Electrolytic copper foil is made of copper sulfate solution. It is electrolyzed in an electrolytic cell with an insoluble material as the anode and a cathode roller that rotates at a constant speed and is immersed in the copper sulfate electrolyte as the cathode. The copper in the solution is deposited on the surface of the cathode roller to form copper foil. After the copper foil is rotated out of the liquid surface with the roller, it is continuously peeled off from the cathode roller, washed, dried, and coiled to form raw foil.
[0003] At present, the preparation of ultra-thin electrolytic copper foil has the following problems: when electrolytic copper foil is used as the negative electrode current collector of lithium-ion batteries, in order to meet the high volume capacity requirements of lithium-ion batteries, the copper foil needs to be as thin as possible. However, in the field of ultra-thin electrolytic copper, especially copper foil with a thickness of less than 6 microns, there is huge technical resistance for every thickness less than 1 micron; when the negative electrode active material is coated on the surface of the copper foil, the surface of the copper foil needs to have appropriate roughness and surface wetting tension to ensure that the negative electrode active material is evenly coated, firmly bonded, and not easy to fall off; the copper foil needs to have good conductivity, corrosion resistance, high elongation and high tensile strength.
[0004] When electrolytic copper foil is used as the negative electrode current collector of lithium-ion batteries, it is required to have high tensile strength on the one hand so that it is not easy to break when coating the negative electrode active material, and on the other hand, it is required to have good ductility so that it can fully contact with the negative electrode active material, reduce the internal resistance of the battery, and improve the safety and capacity of the battery. However, the thinner the electrolytic copper foil, the more the safety performance and cycle life of the lithium battery will decrease. It is very difficult to achieve extremely thin copper foil, high tensile strength, high elongation, low roughness, and excellent oxidation resistance at the same time.
[0005] Therefore, it is of great significance to study and obtain an extremely thin electrolytic copper foil with high mechanical properties, low roughness and good oxidation resistance. Summary of the invention
[0006] The object of the present invention is to provide an electrolyte for an ultra-thin electrolytic copper foil and an ultra-thin electrolytic copper foil and a preparation method thereof in view of the deficiencies in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides an electrolyte for an ultra-thin electrolytic copper foil, the electrolyte comprising copper sulfate, an inorganic acid, an additive, a complexing agent, a conductive polymer and hydrolyzed collagen;
[0009] In the electrolyte, the mass concentration of copper sulfate is 175-260 g / L, the mass concentration of inorganic acid is 80-100 g / L, the mass concentration of additive is 1-5 g / L, the mass concentration of complexing agent is 3-8 g / L, the mass concentration of conductive polymer is 0.5-3 g / L, and the mass concentration of hydrolyzed collagen is 0.1-0.5 g / L.
[0010] Preferably, the inorganic acid is sulfuric acid, nitric acid, hydrofluoric acid or aminosulfonic acid.
[0011] Preferably, the additive comprises a grain refiner and a non-ionic surfactant, and the mass ratio of the grain refiner to the non-ionic surfactant is 3-6:1-3.
[0012] Preferably, the grain refiner comprises one or more of sodium polydisulfide propane sulfonate, sodium 4-[[2-(acetylamino)ethyl]dithio]-1-butanesulfinate, sodium 3-mercapto-1-propane sulfonate and ethylenethiourea, and the nonionic surfactant is fatty amine polyoxyethylene ether or fatty alcohol polyoxyethylene ether.
[0013] Preferably, the complexing agent comprises one or more of potassium sodium tartrate, sodium tartrate, sodium pyrophosphate and cysteine.
[0014] Preferably, the conductive polymer comprises one or more of polypyridine, polyacetylene and polyaniline; and the molecular weight of the hydrolyzed collagen is 1300 to 3000 Daltons.
[0015] The present invention also provides a method for preparing an ultra-thin electrolytic copper foil from the electrolyte of the ultra-thin electrolytic copper foil, comprising the following steps:
[0016] The electrolyte is placed in the anode tank for electrochemical reaction, and copper is deposited on the cathode roller to obtain an extremely thin electrolytic copper foil.
[0017] Preferably, the temperature of the electrochemical reaction is 55-65°C, and the current density is 55-70A / dm 2 .
[0018] The present invention also provides an ultra-thin electrolytic copper foil prepared by the preparation method, wherein the ultra-thin electrolytic copper foil has a thickness of 2.7 to 3.8 μm, a tensile strength of ≥620 MPa, and an elongation of ≥8.2%.
[0019] The beneficial effects of the present invention include:
[0020] The components in the electrolyte of the present invention interact with each other, and by controlling the components and concentrations of the electrolyte and the electrodeposition process parameters, the thickness and roughness of the copper foil are significantly reduced, while the mechanical properties, anti-oxidation properties and electrochemical properties of the copper foil are improved. The ultra-thin copper foil of the present invention can solve the problem of edge tearing of the cathode roller, not only reducing the thickness of the copper foil, but also enabling continuous production without edge tearing, achieving a double breakthrough in the ultra-thin thickness of the copper foil and mechanical properties. DETAILED DESCRIPTION
[0021] The present invention provides an electrolyte for an ultra-thin electrolytic copper foil, the electrolyte comprising copper sulfate, an inorganic acid, an additive, a complexing agent, a conductive polymer and hydrolyzed collagen;
[0022] In the electrolyte, the mass concentration of copper sulfate is 175-260 g / L, the mass concentration of inorganic acid is 80-100 g / L, the mass concentration of additive is 1-5 g / L, the mass concentration of complexing agent is 3-8 g / L, the mass concentration of conductive polymer is 0.5-3 g / L, and the mass concentration of hydrolyzed collagen is 0.1-0.5 g / L.
[0023] The electrolyte of the present invention contains copper sulfate at a mass concentration of 175 to 260 g / L, preferably 185 to 240 g / L, more preferably 195 to 220 g / L, and even more preferably 205 to 210 g / L.
[0024] The electrolyte of the present invention contains an inorganic acid at a mass concentration of 80 to 100 g / L, preferably 85 to 98 g / L, more preferably 88 to 95 g / L, and even more preferably 90 to 92 g / L.
[0025] In the present invention, the inorganic acid is preferably sulfuric acid, nitric acid, hydrofluoric acid or aminosulfonic acid.
[0026] In the present invention, copper sulfate and inorganic acid are main components of the electrolyte. If the concentration of copper sulfate is too low, the plating layer in the high current area is easy to burn; if the concentration of copper sulfate is too high, the dispersibility and leveling capabilities of the electrolyte will be reduced; the function of the inorganic acid is to improve the conductivity of the solution, prevent the hydrolysis of copper salt, and make the plating layer crystallized fine. If the concentration of the inorganic acid is too low, the conductivity of the solution is poor, resulting in a decrease in the dispersibility of the plating solution; if the concentration of the inorganic acid is too high, the mobility of copper ions is reduced, the electroplating efficiency is reduced, the ductility of the copper plating layer is reduced, and the brightness of the plating layer is also reduced.
[0027] The electrolyte of the present invention contains additives at a mass concentration of 1 to 5 g / L, preferably 2 to 4 g / L, more preferably 2.5 to 3.5 g / L, and even more preferably 3 g / L.
[0028] In the present invention, the additive preferably comprises a grain refiner and a nonionic surfactant, and the mass ratio of the grain refiner to the nonionic surfactant is preferably 3-6:1-3, more preferably 4-5:1.5-2.5, and more preferably 4.5:2.
[0029] In the present invention, the grain refiner preferably comprises one or more of sodium polydisulfide dipropane sulfonate, sodium 4-[[2-(acetylamino)ethyl]dithio]-1-butanesulfinate, sodium 3-mercapto-1-propane sulfonate and ethylene thiourea; the nonionic surfactant is preferably fatty amine polyoxyethylene ether or fatty alcohol polyoxyethylene ether; the fatty amine polyoxyethylene ether is preferably fatty amine polyoxyethylene ether AC-1800 series, and further preferably fatty amine polyoxyethylene ether AC-1860, fatty amine polyoxyethylene ether AC-1815 or fatty amine polyoxyethylene ether AC-1830; the fatty alcohol polyoxyethylene ether is preferably fatty alcohol polyoxyethylene ether AEO-9, fatty alcohol polyoxyethylene ether AEO-3 or fatty alcohol polyoxyethylene ether AEO-4.
[0030] In the present invention, the grain refiner has a brightening effect, the nonionic surfactant can lubricate the electrode, promote the adsorption of various components of the electrolyte on the cathode, and can also reduce the surface tension of the electrolyte and improve the migration ability of the electrolyte.
[0031] The electrolyte of the present invention contains a complexing agent at a mass concentration of 3 to 8 g / L, preferably 4 to 7 g / L, and more preferably 5 to 6 g / L.
[0032] In the present invention, the complexing agent preferably comprises one or more of potassium sodium tartrate, sodium tartrate, sodium pyrophosphate and cysteine.
[0033] In the present invention, the grain refiner, complexing agent, and nonionic surfactant are added in a reasonable ratio to significantly improve the mechanical properties and oxidation resistance of the ultra-thin electrolytic copper foil and reduce the roughness. If the amount of the grain refiner is too small, the roughness of the electrolytic copper foil increases and the surface wettability deteriorates. If the amount of the grain refiner is too large, the deposition and crystallization of copper ions are inhibited, and the electrolysis efficiency is reduced. If the nonionic surfactant is too small, the system dispersibility is reduced and the mechanical properties of the copper foil are reduced. If the nonionic surfactant is too large, the adsorption of electrolyte components on the cathode and the deposition of copper ions are hindered, resulting in a decrease in the performance of the copper foil.
[0034] The electrolyte of the present invention contains a conductive polymer at a mass concentration of 0.5 to 3 g / L, preferably 0.8 to 2.5 g / L, more preferably 1 to 2 g / L, and even more preferably 1.3 to 1.5 g / L.
[0035] In the present invention, the conductive polymer preferably comprises one or more of polypyridine, polyacetylene and polyaniline; polypyridine is preferably poly(4-vinylpyridine) or poly(3,5-pyridine).
[0036] The poly(4-vinylpyridine) or poly(3,5-pyridine) of the present invention produces an adsorption effect with the cathode, has a low steric hindrance, and improves the leveling effect and electrolysis efficiency, reduces the surface roughness of the copper foil, and improves the surface wettability. If the amount of the conductive polymer is too small, the surface roughness of the copper foil increases. If the amount of the conductive polymer is too large, the excessive positive charge will break the ion balance of the electrolyte, resulting in unstable electrolyte performance, uneven copper foil thickness, and increased roughness.
[0037] The electrolyte of the present invention contains hydrolyzed collagen at a mass concentration of 0.1 to 0.5 g / L, preferably 0.2 to 0.4 g / L, and more preferably 0.3 g / L.
[0038] In the present invention, the molecular weight of the hydrolyzed collagen is preferably 1300 to 3000 Daltons, more preferably 1500 to 2500 Daltons, and even more preferably 1800 to 2200 Daltons.
[0039] The present invention also provides a method for preparing an ultra-thin electrolytic copper foil from the electrolyte of the ultra-thin electrolytic copper foil, comprising the following steps:
[0040] The electrolyte is placed in the anode tank for electrochemical reaction, and copper is deposited on the cathode roller to obtain an extremely thin electrolytic copper foil.
[0041] In the present invention, the temperature of the electrochemical reaction is preferably 55 to 65°C, more preferably 58 to 63°C, and more preferably 60 to 61°C; the current density is preferably 55 to 70 A / dm 2 , more preferably 58 to 66 A / dm 2 , more preferably 60 to 63 A / dm 2 .
[0042] In the electrochemical reaction of the present invention, the anode material is preferably a titanium-iridium-plated material, a titanium-based material coated with platinum metal oxide, or a lead-antimony alloy, the cathode material is preferably titanium, aluminum, or a titanium alloy, and the flow rate of the electrolyte is preferably 18 to 25 m / s. 3 / h, more preferably 20 to 24 m 3 / h, more preferably 22 to 23 m 3 / h.
[0043] In the present invention, after the cathode roller deposits copper, the foil surface is preferably cleaned with deionized water and then dried at 60-80°C, and then the copper foil is passivated with a potassium dichromate solution. The molar concentration of the potassium dichromate solution is preferably 0.02-0.05 mol / L, more preferably 0.03-0.04 mol / L, and more preferably 0.035 mol / L.
[0044] The passivation treatment of the present invention generates a very thin, dense, and well-adhesive passivation film on the metal surface, which effectively prevents the copper foil from being oxidized, improves the flexibility and elongation of the copper foil, and reduces the thickness of the copper foil.
[0045] The present invention also provides an ultra-thin electrolytic copper foil prepared by the preparation method. The ultra-thin electrolytic copper foil preferably has a thickness of 2.7 to 3.8 μm, a tensile strength of ≥620 MPa, and an elongation of ≥8.2%.
[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0047] Example 1
[0048] The electrolyte of the ultra-thin electrolytic copper foil is composed of copper sulfate, sulfuric acid, additives, potassium sodium tartrate, polyacetylene, hydrolyzed collagen and deionized water. In the electrolyte, the mass concentration of copper sulfate is 185g / L, the mass concentration of sulfuric acid is 85g / L, the mass concentration of additives is 1.5g / L (the additive is composed of sodium polydisulfide dipropane sulfonate and fatty amine polyoxyethylene ether AC-1860 with a mass ratio of 3:1), the mass concentration of potassium sodium tartrate is 3g / L, the mass concentration of polyacetylene is 0.8g / L, and the mass concentration of hydrolyzed collagen (molecular weight 1300 Daltons) is 0.1g / L.
[0049] With the titanium-coated iridium plate as the anode and the aluminum plate as the cathode, the electrolyte is placed in the anode tank for electrochemical reaction until copper is crystallized and deposited on the cathode roller. During the electrochemical reaction, the temperature is 57°C and the current density is 55A / dm 2 , the flow rate of the electrolyte is 19m 3 After the copper deposition is completed, the copper foil is peeled off, washed with deionized water and dried at 65°C, and then immersed in a 0.02 mol / L potassium dichromate aqueous solution for passivation for 20 seconds to obtain an ultra-thin electrolytic copper foil with a thickness of 3.7 μm.
[0050] Example 2
[0051] The electrolyte of the ultra-thin electrolytic copper foil is composed of copper sulfate, aminosulfonic acid, additives, cysteine, polyaniline 5612-44-2, hydrolyzed collagen and deionized water. In the electrolyte, the mass concentration of copper sulfate is 255 g / L, the mass concentration of aminosulfonic acid is 95 g / L, the mass concentration of the additive is 4.5 g / L (the additive is composed of 4-[[2-(acetylamino)ethyl]dithio]-1-butanesulfinate sodium and fatty alcohol polyoxyethylene ether AEO-9 in a mass ratio of 5:3), the mass concentration of cysteine is 7 g / L, the mass concentration of polyaniline 5612-44-2 is 2.5 g / L, and the mass concentration of hydrolyzed collagen (molecular weight 2800 Daltons) is 0.4 g / L.
[0052] The titanium substrate coated with platinum metal oxide is used as the anode and the titanium plate is used as the cathode. The electrolyte is placed in the anode tank for electrochemical reaction until copper is crystallized and deposited on the cathode roller. During the electrochemical reaction, the temperature is 62°C and the current density is 65A / dm 2 , the flow rate of the electrolyte is 25m 3 After the copper deposition is completed, the copper foil is peeled off, washed with deionized water and dried at 75°C, and then immersed in a 0.04 mol / L potassium dichromate aqueous solution for passivation for 15 seconds to obtain an extremely thin electrolytic copper foil with a thickness of 3.3 μm.
[0053] Example 3
[0054] The electrolyte of the ultra-thin electrolytic copper foil is composed of copper sulfate, sulfuric acid, additives, sodium pyrophosphate, poly (4-vinyl pyridine), hydrolyzed collagen and deionized water. In the electrolyte, the mass concentration of copper sulfate is 215g / L, the mass concentration of sulfuric acid is 90g / L, the mass concentration of the additive is 3g / L (the additive is composed of sodium 3-mercapto-1-propane sulfonate and fatty amine polyoxyethylene ether AC-1830 with a mass ratio of 5:2), the mass concentration of sodium pyrophosphate is 5g / L, the mass concentration of poly (4-vinyl pyridine) is 1.6g / L, and the mass concentration of hydrolyzed collagen (molecular weight 2000 Dalton) is 0.25g / L.
[0055] With the lead-antimony alloy plate as the anode and the titanium alloy plate as the cathode, the electrolyte is placed in the anode tank for electrochemical reaction until copper is crystallized and deposited on the cathode roller. During the electrochemical reaction, the temperature is 60°C and the current density is 62A / dm 2 , the flow rate of the electrolyte is 23m 3 After the copper deposition is completed, the copper foil is peeled off, washed with deionized water and dried at 70°C, and then immersed in a 0.03 mol / L potassium dichromate aqueous solution for passivation for 15 seconds to obtain an extremely thin electrolytic copper foil with a thickness of 2.8 μm.
[0056] Comparative Example 1
[0057] The poly(4-vinylpyridine) and fatty amine polyoxyethylene ether AC-1830 of Example 3 were omitted, the additive was sodium 3-mercapto-1-propane sulfonate, the mass concentration of copper sulfate was 120 g / L, and the current density was 45 A / dm 2 , other conditions were the same as those in Example 3, and an ultra-thin electrolytic copper foil with a thickness of 6.2 μm was obtained.
[0058] Comparative Example 2
[0059] The sodium pyrophosphate and hydrolyzed collagen in Example 3 were omitted, the mass concentration of the additives was 0.3 g / L, the passivation treatment step of the copper foil was omitted, and the other conditions were the same as in Example 3, to obtain an ultra-thin electrolytic copper foil with a thickness of 5.8 μm.
[0060] The roughness, tensile strength, elongation and oxidation resistance of the electrolytic copper foil prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested. Roughness (ten-point average roughness, Rz): Measured using an α-type surface roughness meter (Kosaka Laboratory, model SE1700) using the IPC-TM-650 method. A CTM2050 microcomputer-controlled electronic universal testing machine was used to perform a room temperature tensile strength test in accordance with the Test Method for Copper Foil for Printed Boards (GB / T 29847-2013), with a tensile speed of 10 mm / min. The elongation was tested in accordance with the GB / T5230-1995 standard. The oxidation resistance test was performed at 140°C for 1 hour.
[0061] The roughness of the matte surface of the ultra-thin electrolytic copper foil prepared in Example 1 is 1.2 μm, and the roughness of the smooth surface is 0.9 μm; the tensile strength is 623 MPa; the elongation is 9.0%; after being kept at 140° C. for 1 hour, no oxidation or discoloration occurs on the surface of the sample.
[0062] The roughness of the matte surface of the ultra-thin electrolytic copper foil prepared in Example 2 is 1.4 μm, and the roughness of the smooth surface is 1.05 μm; the tensile strength is 630 MPa; the elongation is 9.5%; after being kept at 140° C. for 1 hour, no oxidation or discoloration occurs on the surface of the sample.
[0063] The roughness of the matte surface of the ultra-thin electrolytic copper foil prepared in Example 3 is 1.1 μm, and the roughness of the smooth surface is 0.9 μm; the tensile strength is 652 MPa; the elongation is 9.8%; after being kept at 140° C. for 1 hour, no oxidation or discoloration occurs on the surface of the sample.
[0064] The roughness of the rough surface of the ultra-thin electrolytic copper foil prepared in Comparative Example 1 is 1.8 μm, and the roughness of the smooth surface is 1.4 μm; the tensile strength is 500 MPa; the elongation is 7.6%; after being kept at 140° C. for 1 hour, oxidation and discoloration occurred on the surface of the sample.
[0065] The roughness of the matte surface of the ultra-thin electrolytic copper foil prepared in Comparative Example 2 is 1.68 μm, and the roughness of the smooth surface is 1.37 μm; the tensile strength is 510 MPa; the elongation is 7.3%; after being kept at 140° C. for 1 hour, oxidation and discoloration occurred on the surface of the sample.
[0066] It can be seen from the examples and comparative examples that the thickness of the electrolytic copper foil of the present invention is significantly reduced, the tensile strength and elongation are significantly improved, and it has good anti-oxidation performance and low surface roughness. The components and concentrations of the electrolyte of the present invention, electrolysis process parameters, passivation treatment, etc. are interrelated. Changing any component or parameter will lead to a decrease in the performance of the electrolytic copper foil.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte for ultra-thin electrolytic copper foil, characterized in that: The electrolyte comprises copper sulfate, inorganic acid, additives, complexing agent, conductive polymer and hydrolyzed collagen; In the electrolyte, the mass concentration of copper sulfate is 175-260 g / L, the mass concentration of inorganic acid is 80-100 g / L, the mass concentration of additive is 1-5 g / L, the mass concentration of complexing agent is 3-8 g / L, the mass concentration of conductive polymer is 0.5-3 g / L, and the mass concentration of hydrolyzed collagen is 0.1-0.5 g / L; The additives are a grain refiner and a nonionic surfactant, and the mass ratio of the grain refiner and the nonionic surfactant is 3-6:1-3; The grain refiner is one or more of sodium polydisulfide dipropane sulfonate, sodium 4-[[2-(acetylamino)ethyl]dithio]-1-butanesulfinate, sodium 3-mercapto-1-propane sulfonate and ethylenethiourea, and the nonionic surfactant is fatty amine polyoxyethylene ether or fatty alcohol polyoxyethylene ether; The conductive polymer is one or more of polypyridine, polyacetylene and polyaniline.
2. The electrolyte according to claim 1, characterized in that The inorganic acid is sulfuric acid, nitric acid, hydrofluoric acid or aminosulfonic acid.
3. The electrolyte according to claim 2, characterized in that The complexing agent comprises one or more of potassium sodium tartrate, sodium tartrate, sodium pyrophosphate and cysteine.
4. The electrolyte according to claim 2 or 3, characterized in that The molecular weight of the hydrolyzed collagen is 1300-3000 Daltons.
5. The method for preparing ultra-thin electrolytic copper foil using the electrolyte of the ultra-thin electrolytic copper foil according to any one of claims 1 to 4, characterized in that: The following steps are included: The electrolyte is placed in the anode tank for electrochemical reaction, and copper is deposited on the cathode roller to obtain an extremely thin electrolytic copper foil.
6. The method according to claim 5, characterized in that The temperature of the electrochemical reaction is 55-65°C, and the current density is 55-70A / dm 2 .
7. The ultra-thin electrolytic copper foil prepared by the method according to claim 5 or 6, characterized in that: The ultra-thin electrolytic copper foil has a thickness of 2.7-3.8 μm, a tensile strength of ≥620 MPa, and an elongation of ≥8.2%.
Citation Information
Cited By
Preparation method of high-resistance low-profile lithium battery copper foil
CN119663382A
Additive of 1-micron electrolytic copper foil and preparation method of 1-micron electrolytic copper foil
CN121915467A
Additive for 1-micron electrolytic copper foil and method for producing 1-micron electrolytic copper foil
CN121915467B